2014
DOI: 10.1093/nar/gkt1358
|View full text |Cite
|
Sign up to set email alerts
|

CpG domains downstream of TSSs promote high levels of gene expression

Abstract: CpG dinucleotides are known to play a crucial role in regulatory domains, affecting gene expression in their natural context. Here, we demonstrate that intragenic CpG frequency and distribution impacts transgene and genomic gene expression levels in mammalian cells. As shown for the Macrophage Inflammatory Protein 1α, de novo RNA synthesis correlates with the number of CpG dinucleotides, whereas RNA splicing, stability, nuclear export and translation are not affected by the sequence modification. Differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 56 publications
5
42
0
Order By: Relevance
“…Consistent with a transcriptional effect of codon usage, it was previously shown that mammalian genes with high GC contents, which means the use of more preferred codons, had higher expression levels than those with lower GC content; this observation was not a result of differences in mRNA degradation rates (50,51). More recently, codon usage was shown to contribute to the balanced expression of Toll-like receptors by affecting transcription rather than translation in mammals (52).…”
Section: H3k9me3 Is Responsible For the Codon Usage-mediated Transcrimentioning
confidence: 67%
“…Consistent with a transcriptional effect of codon usage, it was previously shown that mammalian genes with high GC contents, which means the use of more preferred codons, had higher expression levels than those with lower GC content; this observation was not a result of differences in mRNA degradation rates (50,51). More recently, codon usage was shown to contribute to the balanced expression of Toll-like receptors by affecting transcription rather than translation in mammals (52).…”
Section: H3k9me3 Is Responsible For the Codon Usage-mediated Transcrimentioning
confidence: 67%
“…The latter can be due to various effects, such as increasing mRNA stability 58 or increasing de novo mRNA synthesis of transgenes. 19,25 For hgfp genes with modified CpG content in the open reading frame, we have previously shown, using T7 polymerase-driven transcription in the cytoplasm of mammalian cells, that modulation of the CpG content does not affect mRNA stability or translational efficiency. 18 To avoid the spreading of repressive epigenetic marks surrounding the integration locus into the proximal transgene and to prevent loss of the transgene through the outgrowth of transgene-lacking cells, transgene expression is optimally conducted under selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Further analyses attributed CpG-mediated expression enhancement in mammalian cells to an increased transcription rate, 18 which correlates with alterations in the chromatin structure and RNA polymerase II elongation rates. 19 Because cytosines in particular in promoter regions are the exclusive targets for methylation in vertebrates, 20 CpGs are often avoided in vector elements and also in transgene sequences to prevent silencing 21 and to provide prolonged transgene expression. 14,[22][23][24] In contrast, it was shown that CpG dinucleotides in the transgene open reading frame can provide improved and long-term transgene expression in mouse tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that many CG-rich sequences in eukaryotic genomes undergo inactivation by methylation, CpG-islands are transcriptionally active [3][4][5]. A twofold increase in the frequency of CpG dinucleotides in the regions of transcriptional initiation of human genes with a high level of transcription was demonstrated recently [6]. This indicates that the 5'-regions of genes with a high content of CpG dinucleotides may be important transcriptional regulatory elements at least in the human genome.…”
Section: Introductionmentioning
confidence: 99%